Research advances of primary glomerulonephritis and pregnancy - Wang Nan; Yang Tao; Hao Qiu-fa; Jiang Bei; Hu Zhao (Linchuang shenzangbing zazhi)
With a rising incidence of primary glomerulonephritis (PGN) and more women pursuing pregnancy at more advanced ages,management of kidney disease in pregnancy has become a common problem for both nephrologists and obstetricians. Women with PGN face several challenges during pregnancy due to their elevated physiologic demands on kidney,such as potential teratogenicity of medications,higher risks of preeclampsia and preterm delivery and progression of kidney disease. How to evaluate the timing of pregnancy in PGN women,monitor and manage the course of pregnancy have remained common concerns for both clinicians and patients. This review summarized the latest findings of PGN women during pregnancy. The topics included risk factors for pregnancy outcomes in PGN,effect of pregnancy on progression of renal disease,different subtypes and drug dosing during pregnancy.